Isolates of entomopathogenic fungi against Trialeurodes vaporariorum west in Uruguay - Rodríguez Dos Santos, A.; Núñez, E. del Pozo (Agrociencia Uruguay, 2003)
Several isolates were obtained from dead nymphs of the greenhouse whitefly, Trialeurodes vaporariorum (West.), with the characteristic symptoms of entomopathogenic fungi, collected at the departments of Canelones, Montevideo and Tacuarembó, in Uruguay. After obtainment of pure cultures, morphologic, macroscopic and microscopic characterization was done, identifying afterwards the isolates, using the keys and descriptions for genera and species. The natural occurrence, in the different departments, of Verticillium lecanii (Zimm.) Viegas, Paecilomyces fumosoroseus (Wize) Brown and Smith and the genera Beauveria as pathogens for T. vaporariorum on tomato in greenhouses, was shown. This constitutes the first report of this kind in this country. An isolate of P. fumosoroseus (Pf-001) and one of V. lecanii (Vl-001) were used to evaluate their virulence on nymphs of T. vaporariorum under laboratory conditions. The LC50 calculated for the isolate Pf-001 was 1.31x104 conidia.ml-1, while for Vl-001 was 4.98x104, which means 3.8 higher. The LT50 calculated for Pf-001 was 73.18 h, while for Vl-001 was 91.12 h, which represents that the first isolate needs 17.9 h less to achieve the same mortality effect.